Horizontal Detection Range Estimation of Deep-Sea Acoustic Shadow Area Based on Vertical Phased Emission Array - Naibin Chen; Dayong Peng; Li Ma; Tao Hu; Haijun Liu; Haifeng Li (Journal of Marine Science and Engineering)
To scan the horizontal range of the deep-sea shadow zone with high accuracy and efficiency, enabling active target detection, a horizontal detection range estimation method based on phased sound focusing technology is presented. The model of the phased emission sound field is derived, along with the theoretical estimation formula for the horizontal detection range, by combining the half-power beamwidth of the beam curve at the phased-emitter end with the ray propagation law of deep-sea acoustics. The corresponding relationships among each discrete phased angle, the horizontal distance, and the detection range of the focused beam boundary are detailed. The estimation formula for the horizontal detection range is then improved to account for the sea surface reflection effect, and angle optimization is applied to the transmitted beam curve to counteract the boundary error accumulation effect of the focused sound beam as the sound ray propagates. To address the issue of reduced scanning efficiency at large phased angles, the grating lobe-focused sound beam generated by phased emission array parameters is used to achieve angle scanning within the close deep-sea sound shadow zone, increasing the phased angle scanning efficiency. Finally, the deep-sea phased emission active target detection experiments were carried out, and the echo signal generated by the phased focused sound beam and received by the vertical receiving array was recorded. Numerical simulation and echo signal processing show that the high-efficiency angle scanning of the entire deep-sea sound shadow zone is achieved by the proposed estimation method.